Finite element analysis on human knee - Nor Akmal , Halim (2013)
Three dimensional model of human knee were developed to clarify the causes of knee joint injuries such as osteoarthritis, bursitis, and ligament tears. The model developed allowed the simulation by the performance of Finite Element Analysis (FEA) of different angles and different forces. The purpose of this study is to evaluate the result of kneeling 60 degree, kneeling 90 degree, and squatting to the knee joint with and without kneepad. However, this study is focused for construction worker such as mining worker. This study was simulated by using Autodesk Simulation Multiphysics to solve the finite element analysis. There are several crucial points to the proper application of numerical method such as the geometry, material properties, and boundary condition must be created to solve the finite element analysis that must have in finite element method. The force applied is at the area patella with the value of 303N, 603 N, and 903 N. The femur bone, tibia bone, and patella are assumed as rigid body. From the result the effect of kneeling 90 degree, kneeling 120 degree flexion, and squatting to the patella., the maximum stress on patella of 90 degree flexion is higher because have larger contact surface area as the knee was bent than 60 degree flexion and 120 degree flexion. For stress vs. deformation for cartilage, the position of 90 degree flexion give the higher stress and deformation as the stress on patella was high the stress to the cartilage became higher the contact stress of patella occur at the superior half of the patella and an area of the femoral groove just above the notch that means the contact stress of patella to cartilage 90 degree flexion was larger than 60 degree and 120 degree flexion. As for ligaments, at 90 degree flexion,the higher stress occur at ACL for without and with kneepad with the value 0.507 MPa and 0.0667 MPa with the percentage of absorption to the kneepad is 86%, followed by PCL 98.5 %. MCL is 99.4%, and LCL 98.5 %. From the result, it is true that the most common ligament injuries in mining or construction worker is ACL tear as the results shows that ACL gives highest stress that other ligaments. PCL had lower stress than ACL as in medical, PCL gives far less common injury than ACL because of PCL function itself that maintaining joint normal function. From the research, it can be concluded that wearing the kneepad will reduce the stress on knee ligament of construction worker to prevent injury and knee pain.